Resource Allocation in a National Dental Service Using Program Budgeting Marginal Analysis. (January 2023) - Vernazza, C.R.; Carr, K.; Holmes, R.D.; Wildman, J.; Gray, J.; Exley, C.; Smith, R.A.; Donaldson, C.
Introduction: In any health system, choices must be made about the allocation of resources (budget), which are often scarce. Economics has defined frameworks to aid resource allocation, and program budgeting marginal analysis (PBMA) is one such framework. In principle, patient and public values can be incorporated into these frameworks, using techniques such as willingness to pay (WTP). However, this has not been done before, and few formal resource allocation processes have been undertaken in dentistry. This study aimed to undertake a PBMA with embedded WTP values in a national dental setting. Methods: The PBMA process was undertaken by a panel of participant-researchers representing commissioners, dentists, dental public health staff, and academics. The panel reviewed current allocations and generated a set of weighted criteria to evaluate services against. Services to be considered for removal and investment were determined by the panel and wider discussion and then scored against the criteria. Values from a nationally representative WTP survey of the public contributed to the scores for interventions. Final decisions on removal and investment were taken after panel discussion using individual anonymous electronic voting. Results: The PBMA process resulted in recommendations to invest in new program components to improve access to general dentists, care home dentistry, and extra support for dental public health input into local government decisions. Disinvestments were recommended in orthodontics and to remove routine scaling and polishing of teeth. Discussion: The PBMA process was successful in raising awareness of resource allocation issues. Implementation of findings will depend on the ability of decision makers to find ways of operationalizing the decisions. The process illustrates practical aspects of the process that future dental PBMAs could learn from. Knowledge Transfer Statement: This study illustrates a framework for resource allocation in dental health services and will aid decision makers in implementing their own resource allocation systems.